THE SOCIAL-PSYCHOLOGICAL ESSENCE OF THE SOURCE OF THE SUFI TEACHING OF KHOJAGON (NAQSHBANDIYA), THE UNIQUE HISTORICAL HERITAGE OF THE FIRST RENAISSANCE PERIOD - Kasimov , Ubaydulla Akhrorovich (Innovative Development in Educational Activities, 2023)
The unique historical heritage of the first renaissance period is the "Hush dar dam" rule of Sufism, which is a unique historical heritage of the first renaissance period. self-control, adjustment, programming, improvement in the realization of behavior, behavior and activity, on the other hand, together form the full content of a single life.